Corporate sustainability impact on reputation and customer behaviour - Jančiauskaitė, Laura; Lasickaitė, Kristina; Ripkauskaitė, Austė (Vilnius University Open Series, 2019)
In a modern world sustainable business development is the adaptation of strategies and actions in order to meet the needs of the organization and society for nature conservation, social welfare and economy. Increasing concern for environmental and social issues commit business to take responsibility and adopt sustainable development principles into strategic management. The research on corporate sustainability examined in this article shows significant relationship of sustainable business between the company's reputation and customers behaviour, while brand image takes the mediating role on all of them. The following theoretical model was created: the impact of corporate sustainability on customer perceived corporate reputation and customer buying decision behaviour shows the relation between these determinants.